Influência da adubação em cana-de-açúcar sobre as bactérias solubilizadoras de fósforo - Campitelli, Lívia Lima [UNESP] (2014)
The use of phosphate solubilizing bacteria can be an alternative to reduce the amount of phosphate fertilizers. The present work examined four different areas that receive different treatments, as follows: soybeans as crop rotation, vinasse and filter cake as fertilizer, compared with control; relating the total number of phosphorus solubilizing bacteria, total bacteria and some soil microbiological parameters for each treatment. Even the organic matter was higher (19.8%) to filter cake area, moisture having greater value (18.9%) to the area of vinasse and total bacteria ranging from 7.1 to 7.4 log10 colony forming units, there was no significant difference between the areas. Dehydrogenase (TFF 593.5μg / 24h.g) and microbial biomass carbon (C 916.7μg / g) were higher in the area of filter cake. The respiratory activity was lower (5.23 mg / 100g of CO2) for soybean area and the concentration of phosphorus was higher (1011.3 g P g-1) to the area of the filter cake. However, the total number of phosphorus solubilizing bacteria was higher (6.03 log10 CFU) in the area of soy and not to the area of the filter cake and vinasse. These results suggest that the use of vinasse and filter cake does not improve the conditions for colonization and establishment of phosphorus solubilizing bacteria and the use of phosphorus solubilizing microorganisms in the filter cake improving the availability of this nutrient , in the case of a possible low-cost alternative